The Effect Of Mefenamic Acid On Longitudinal Development Of Growth Plate In Young Male White Rats - Hasan, Muhamad (Journal of Agromedicine and Medical Sciences, 2016)
The past epidemiologic studies did not have definite explanation about the effect of consuming Mefenamic Acid on Longitudinal Bone Development. The aim of this study is to explain the effect of Mefenamic Acid on Longitudinal Bone Development. The design of this study was the Separate pretest, Posttest Only Control Group Design using 40 male wistar strain rats and divided into four groups. They consists of one pretest group, one control group and two treatment groups. The treatment groups were given mefenamic acid orally in the dose of 27 mg/200 g BW/day, and 54 mg/200 g BW/day which were dissolved in 2 ml of distilled water. After 4 weeks, the length of femur, length of growth plate and number of longitudinal cell of growth plate are noticed. The result was showed in all of experimental animals had a significant difference to control groups (p<0.05). Pair wise comparisons showed that significant difference (p<0.05) occurred in all of groups except between mefenamic acid 27 mg and mefenamic acid 54 mg that not significant difference. This study show that mefenamic acid treatment cause decrease of femur length, decrease of growth plate length and decrease number of growth plate cell. Keywords: mefenamic acid, chondrocyte, growth plate